Pyroelecticity in cadmium Zinc telluride. (Journal of Science and Technology, 2016)
The dynamic method has been used to study pyroelectricity in Cd0.9  Zn0.1,Te. Transient cur-rents produced in a single crystal of Cd0.9  Zn0.1,Te when subjected to flashes of light are shown to be pyroelectric in origin. The pyroelectric cur-rent was found to increase with temperature until it reached a peak and dropped beyond the transition temperature which was found to be 1 1 8°C. This is the first time that pyroelectricity is reported in a material that crystallizes in the zinc blende configuration in the first approximation.